Comprehensive preventive treatments for episodic migraine: a systematic review of randomized clinical trials - María-Karina Vélez-Jiménez; Adriana Patricia Martínez-Mayorga; Adriana Patricia Martínez-Mayorga; Ildefonso Rodriguez-Leyva; Ildefonso Rodriguez-Leyva; Marisol Jannet Figueroa-Medina; Maria Teresa Reyes-Alvarez; Juan Carlos Pérez-García; Rubén Darío Vargas-García; Daniel San-Juan; Mauricio Pierdant-Perez; Emilio García Gómez; et al. (Frontiers in Neurology)
BackgroundEpisodic migraine is a prevalent and disabling neurological disorder with a significant impact on quality of life and productivity. Preventive treatment aims to reduce the frequency, intensity, and disability associated with migraine attacks. However, the comparative efficacy and safety of available preventive strategies remain insufficiently addressed in the literature, especially in low- and middle-income countries.ObjectiveTo evaluate the efficacy and safety of pharmacological and non-pharmacological preventive treatments for episodic migraine through a systematic review and meta-analysis of randomized controlled trials (RCTs).MethodsFollowing PRISMA guidelines, a comprehensive literature search was conducted across Wiley Online, BVS, MEDLINE, and OVID databases through November 2024. Eligible studies were RCTs comparing preventive treatments with placebo or active comparators in adults with episodic migraine. This review was not registered in PROSPERO due to institutional constraints at the time of project initiation. Primary outcomes included changes in monthly migraine days (MMD), monthly headache days (MHD), acute medication days (AMD), adverse events (AE) and serious adverse events (SAE). Meta-analysis was performed using fixed- or random-effects models depending on heterogeneity.ResultsThirty-nine RCTs involving over 15,000 patients were included. Anti-CGRP monoclonal antibodies and gepants demonstrated the most consistent reduction in MMD (−3.2 to −4.4 days) with favorable tolerability. Traditional agents such as topiramate and propranolol showed modest efficacy with higher AE rates. Combination therapies offered superior MMD reductions (up to −5.1 days) but were associated with increased side effects. Non-pharmacological interventions (e.g., neuromodulation, acupuncture) showed promising results but lacked standardization. Meta-analysis of allopathic treatments revealed a significant MMD reduction vs. placebo (−1.25 days; 95% CI − 1.47 to −1.04; p < 0.001).ConclusionCGRP-targeted therapies and gepants are effective first-line options for episodic migraine prevention. Combinations may enhance efficacy but at the cost of tolerability. Non-pharmacological treatments represent useful adjuncts. These findings support individualized, multimodal preventive strategies, particularly in resource-limited settings. However, interpretation should consider potential publication and language bias, as well as the short follow-up duration in many included trials.